STATE MANAGEMENT OF INNOVATION (INSTITUTIONAL ASPECTS) - Shepelenko E.G. (Pressing Problems of Public Administration, 2015)
The article deals with the main stages of theoretical and methodological understanding ofthe problems of innovative practices in terms of participation in innovative activities of variousinstitutions, first of all, with institutions of the state policy. It is emphasized that marketmechanisms without state regulation of the economy are not able to combine private businessinterests with the interests of society as a whole, have a positive impact on the harmonioussustainable development. Historical background of formation of state regulation of innovativeprocesses is relevant at this stage of theoretical understanding of the role of the state as a socialinstitution, the definition of effective mechanisms of state influence on the innovation processes.